STUDI EKSPERIMEN BENTUK KACA PENUTUP UNTUK MENINGKATKAN PRODUKTIFITAS DAN EFISIENSI SOLAR STILL - Nova Risdiyanto Ismail; Andi Hardianto (ROTOR, 2016)
Based on the previous research, it’s needed a research on the development of solar distillation model. The development of a concrete absorbed plate with fin has been conducted and resulted on improving productivity and efficiency of solar still. The development is continued by making a model using the glass covered model with roof shape and V. Experimental method is used in this work. Absorbent plate from concrete with fins models and some gravel are used in this solar still research. The concrete composition is determined by two parts of iron sand and one part of PCC cement. The cover glass design is determined by roof model, V model and conventional model (flat model). Water volume is designed as varied variables. The results show that V model can increase the productivity of freshwater and efficiency of the solar still compared with roof model and conventional model under different water volume. The absorber plate temperature, water temperature and cover glass temperature satisfy the solar radiation pattern. Keywords: solar distillation, cover glass shape, water volume